Hydropneumothorax Revealing a Pneumoblastoma in Children - Karima El Fakiri; Ghizlane Draiss; Noureddine Rada; Mohammed Bouskraoui; Abderrachid Hamdaoui; Mohamed Oulad Saiad (Case Reports in Pediatrics)
Pneumoblastoma is a rare primary childhood tumor. We report the observation of an infant aged 2 years and 8 months who presented with dry cough and dyspnea. The physical examination found mixed pleural effusion syndrome on the right. The chest X-ray revealed a right pneumothorax. Biology has shown leukocytosis at 16,000/mm3. The CT scan revealed parenchymal air cystic lesions affecting the outer segment of the middle lobe mimicking a pulmonary malformation. Thoracic drainage brought back 100 ml of the fluid. Two months later, when a pyopneumothorax appeared, a medium lobectomy was performed. Pathological study specimen showed a high-grade type II pneumoblastoma The extension assessment identified a secondary hepatic location. Chemotherapy has been indicated. This observation illustrates the diagnosis challenge of pneumoblastoma in children.